Impact of alkali-silica reaction and delayed ettringite formation-induced cracking on air permeability and water diffusivity in concrete - Joe Maalouf; Hugo Cagnon; Jérôme Verdier; Stéphane Multon; Jacques Jabbour; David Bouhjiti (Case Studies in Construction Materials)
Managing the effects of Internal Swelling Reactions (ISR), Delayed Ettringite Formation (DEF), and Alkali-Silica Reaction (ASR) on the integrity of concrete structures with containment functions, such as nuclear facilities and dams, remains a major challenge for both long-term operation and maintenance. However, the effect of cracking caused by ISR on the mass transport properties of concrete has not been extensively investigated. To date, there is limited characterization of water diffusive phenomena and permeability in concretes affected by ISR. To address these gaps, a comprehensive and complete characterization of mass transport properties evaluating water porosity, pore distribution, diffusivity, and apparent air permeability in concrete affected by ASR and DEF is conducted hereafter. This experimental work points out the impact of cracking induced by expansion on these parameters. Water diffusivity is multiplied by a maximum of 2.8 for 0.22 % expansion in DEF, while permeability can be multiplied by 44 for ASR concrete after expansion to 0.22 %. The cracking patterns induced by ASR and DEF are different, leading to differences in the evolution of transport properties. Overall, crucial experimental insights to enhance existing models are thus highlighted, particularly concerning the intricate relationship between expansion advancement, cracking, and mass transport properties in concrete.